2006
DOI: 10.1007/s11255-006-9125-2
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between serum prostate specific antigen levels and asymptomatic inflammatory prostatitis

Abstract: High serum PSA levels may correlate with asymptomatic inflammatory prostatitis with high aggressiveness score in BPH patients without clinical prostatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 24 publications
3
33
1
1
Order By: Relevance
“…PSA might be affected by prostate volume, the grade and stage of neoplasms, patient age, and ethnicity (Partin et al, 1990). Several studies reported that the extent and grade of inflammation were correlated positively with serum PSA levels (Kandirali et al, 2007;Ozden et al, 2007). We also reported that PSA levels were positively correlated with NLR which confirms the association of inflammation and PSA.…”
Section: Discussionsupporting
confidence: 78%
“…PSA might be affected by prostate volume, the grade and stage of neoplasms, patient age, and ethnicity (Partin et al, 1990). Several studies reported that the extent and grade of inflammation were correlated positively with serum PSA levels (Kandirali et al, 2007;Ozden et al, 2007). We also reported that PSA levels were positively correlated with NLR which confirms the association of inflammation and PSA.…”
Section: Discussionsupporting
confidence: 78%
“…As reported in several studies, the extent of inflammation and grade correlated positively with the serum PSA level (28,29). Probably in the Group II we have selected patients with lower extension and grade of flogosis: this finding is also supported by the fact that between the two subsets there were no statistical significant differences in terms of total PSA.…”
Section: Discussionsupporting
confidence: 63%
“…Some of these studies found that tPSA levels were significantly higher in patients with prostatitis; however, others failed to support that conclusion, stating that there was no significant association between the existence of prostatitis and tPSA levels, age and prostatic volume. [19][20][21][22][23] In the present study, neither prostatic pathology and tPSA nor age and tPSA were found to be related.…”
Section: Discussioncontrasting
confidence: 82%